A critical review of the rise of the neoliberal concept in economic policy - Ignjatović, Jelena; Filipovic, Sanja (Sociološki pregled, 2022)
In the 1980s, the neoliberal concept was imposed as an economic-political doctrine based on the claim that the free market efficiently allocated resources and ensured world prosperity and peace. The aim of this paper is to try to provide one of the possible interpretations of neoliberal economy on the basis of the analysis of the development of economic thought. The foundations of liberal economy are defined by classical political economy, and the contribution was made by the neoclassical school of economics, but also other directions in the development of economic thought. Although proponents of the neoliberal economy have advocated liberalization and privatization to improve the general well-being of society, the global economic crisis and the COVID-19 crisis have shown the misconceptions and contradictions of neoliberal results that are not only ineffective in times of crisis but also contribute to global inequality.
Keywords: neoliberal economy; economic policy; free market